Bước đầu phân tích tài liệu động đất ghi bằng mạng máy K2 dọc đới Sông Hồng (1997-1999) - Toàn, Đinh Văn; Tsai, Y. Ben; Wu, Hsin Hung; Bắc, Trịnh Việt; Yêm, Nguyễn Trọng; Văn, Phan Thị Kim (Vietnam Journal of Earth Sciences, 2000)
Preliminary interpretation of the earthquake data recorded by the K2 - network along the Red River Fault zone in Vietnam ( 1997 - 1999)